Do critically ill elderly patients show a different profile than younger patients in terms of prealbumin response to nutrition? Prealbumin response of critically ill elderly patients - Ozgultekin, Asu; Dokuyucu, Ayfer (Progress in Nutrition, 2019)
Nutritional assessment is essential for the clinical nutrition practice.In critical care, prealbumin is still a useful marker for this purpose.Geriatric patient population is increasing in number in critical care and with accompanying comorbidities, they exert different treatment-response profiles.We analysed prealbumin response of critically ill elderly patients compared to younger patients. Methods: 1311 adult patients were included in the 5 years retrospective analysis in our tertiery medical-surgical ICU.Admission levels of prealbumin, albumin, C-reactive protein, as well as CRP/albumin and CRP/prealbumin ratios were compared between the young (